Operational and thermodynamic methodology for integrating a gas–steam cycle into a legacy coal-fired power block - Strušnik, Dušan (Journal of Energy Technology, 2026)
This paper investigates the thermodynamic integration of a gas–steam combined cycle into an existing coal-fired power block with the objective of reducing coal utilisation and associated emissions. In the baseline configuration, the legacy unit relies entirely on pulverised coal combustion, whereas the retrofit concept introduces a natural gas-fired gas turbine with heat recovery steam generation. The recovered exhaust heat is used to supplement steam production for the existing steam turbine train, thereby increasing the overall cycle efficiency and enabling partial fuel substitution. From an ecological perspective, natural gas presents a significantly lower carbon emission factor compared to coal, resulting in a proportional reduction of CO₂ and other greenhouse gas emissions at the system level. Additional benefits include lower NOₓ formation due to cleaner combustion and improved operational flexibility, enabling more efficient load following under variable renewable penetration. The results suggest that such hybridisation offers a viable decarbonisation pathway for thermal assets by leveraging the existing infrastructure while achieving meaningful reductions in specific emissions.